Using accrual-based model to test the relationship between earnings management and corporate performance in the Vietnamese stock market - Nguyen, Ha Linh; Nguyen, Dao Thi; Le, Thi Ngoc Phuong; Nguyen, Linh Thuy; Vu, Thu Thi Minh (International Journal of Innovative Research and Scientific Studies, 2025)
The study in this paper examines the influence of earnings management through accruals on the performance of Vietnamese stock market firms based on a panel of 330 HOSE-listed non-financial companies from 2018 to 2022. Discretionary accruals, estimated from the Modified Jones Model, are the proxy for earnings manipulation. Firm performance is gauged by both accounting-based indicators, Return on Assets (ROA) and Return on Equity (ROE), and a market-based measure, Tobin’s Q. Employing fixed-effects panel regression to control for firm-specific heterogeneity and macroeconomic volatility, the findings indicate a significant and consistent negative association between discretionary accruals and all performance measures. Robustness tests using lagged accruals, Kothari’s model performance-matched approach, and subsample tests by size of firm confirm the findings. These results suggest that earnings management comes at the cost of profitability and firm value, particularly for smaller firms that have poorer governance. The research contributes to the literature on financial transparency in emerging markets by providing empirical evidence on the costs of earnings manipulation. Implications are drawn for policymakers, auditors, and investors aiming to strengthen market discipline and reporting quality in Vietnam’s capital market.